Floristic diversity of a Voluntary Natural Reserve (VNR) of Sucrivoire on the right bank of the Bandama river in Zuenoula, in the West Centre of Côte d’Ivoire. - Claude, Kouassi Kouadio; Innocent, Adji Beda; Karidia, Traoré (International Journal of Environment, Agriculture and Biotechnology, 2019)
Several surveys and inventories were conducted with surface survey method using plots, measuring 200 m2 and supplemented with mobile method in Sucrivoire Voluntary Natural Reserve on the right bank of the Bandama river. The analysis of the data collected focused on diversity and floristic richness and used phytoecological methods such as the ACP. The obtained results concern 200 identified botanical species among which 81 % of dicotyledone and 19 % of monocotyledone belonging to 152 genera and 56 families. The ecological factor most pronouncement being the toposequence, the determination of the diversity indices of various strata showed that for each of it the flora is very diversified and homogeneous in general such as indicated by the coefficient of similarity of Sørensen which remains upper to 50 %. However, this flora is dominated by the families of Euphorbiaceae, Poaceae, Rubiaceae, Mimosaceae, Asteraceae, Caesalpiniaceae and Sterculiaceaes which characterize his phytogeographique position. In this floral diversity, the ACP revealed a single group of floral procession, which mean that the three strata constitute a single forest block dominated by Phanerophytes in 66,33 % and containing 12 species with particular status and 17 species considered as commercial forest essences. All these characteristics confirm the good state of preservation of the flora of the right bank of the Bandama river set up as a Voluntary Natural Reserve by Sucrivoire. This sugar canne structure so makes the flora of this site one of the reservoir of biodiversity of the future green frame of Côte d’Ivoire